MORPHOLOGICAL CHANGES OF SENSORIMOTOR CORTEX AND HIPPOCAMPUS IN RATS OF DIFFERENT AGE AFTER TRAUMATIC BRAIN INJURY - Михальський, С.А.; Савіцька, Д.В.; Білошицький, В.В.; Квітницька-Рижова, Т.Ю. (World of Medicine and Biology, 2014)
In the model of severe traumatic brain injury (TBI) in adult and old Wistar rats we have demonstrated significant changes in the structure of sensorimotor cortex and hippocampus, resulting in a significant decrease in the number of neurons, growth of vacuolated hyperchromic nerve cells fraction and the sharp increase in the number of glia. Gene therapy by means of cationic liposome-mediated APOE3 transfer significantly decreased reactive gliosis and number of microgliocytes both in the cortex and in the hippocampus, and had a positive effect on the number of neurons, preventing their loss in adult and especially in old rats.
Keywords: traumatic brain injury; gene therapy; cortex; hippocampus; structural changes; morphometry; age characteristics